Prognosis of Cerebral Arteriopathy in Stroke - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The evolution of cerebral arteriopathy in 50 children with first arterial ischemic stroke (AIS) was evaluated at Great Ormond Street Hospital for Children, and Neuroscience Unit, Institute of Child Health, London.